2007
DOI: 10.1007/s10661-007-9669-3
|View full text |Cite
|
Sign up to set email alerts
|

Variations in sensitivity of two populations of Corophium Orientale (Crustacea: Amphipoda) towards cadmium and sodium laurylsulphate

Abstract: The aim of this work was to monitor the sensitivity of two populations of Corophium orientale (Crustacea: Amphipoda) living at the outfall of two rivers (Magra and Serchio), comparing their responses towards two different toxicant solutions. Sensitivity was monthly checked performing the 96h-LC50 static water only test with Cd(NO3)2 and SDS. If no significant differences were found between the two populations, they could have been employed without distinction to perform sediment toxicity bioassays. As regard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
2
0
0
2
Order By: Relevance
“…Water Quality-Determination of acute toxicity of marine or estuarine sediments to amphipods'. The mortality registered in the negative control group (one dead organism in each replica, 4%) was in agreement with acceptable range reported in literature; as a positive control toxicity was measured with [Cd(NO 3 ) 2 ·4H 2 O] which yielded a LC 50 value of 2.08 mg L −1 and the data were also in good agreement with results reported in Lera et al [17] for this species. In this study, the authors reported LC 50 values with 95% confidence limits for cadmium referring to two different populations of C. orientale in the range of 1.34-7.23 mg L −1 for a population from the River Serchio (Italy) and 1.21-5.39 mg L −1 for a population from the River Magra.…”
Section: Resultssupporting
confidence: 91%
“…Water Quality-Determination of acute toxicity of marine or estuarine sediments to amphipods'. The mortality registered in the negative control group (one dead organism in each replica, 4%) was in agreement with acceptable range reported in literature; as a positive control toxicity was measured with [Cd(NO 3 ) 2 ·4H 2 O] which yielded a LC 50 value of 2.08 mg L −1 and the data were also in good agreement with results reported in Lera et al [17] for this species. In this study, the authors reported LC 50 values with 95% confidence limits for cadmium referring to two different populations of C. orientale in the range of 1.34-7.23 mg L −1 for a population from the River Serchio (Italy) and 1.21-5.39 mg L −1 for a population from the River Magra.…”
Section: Resultssupporting
confidence: 91%
“…The obtained half maximal effective concentration (EC 50 ) values fell within the ranges of 0.42-1.16 mg·L −1 and 1.21-7.23 mg·L −1 reported by Onorati et al [30] and Lera et al [31], for V. fischeri and C. orientale, respectively. …”
Section: Toxicity Testingsupporting
confidence: 83%
“…Al comparar nuestros resultados en S. bicuspis con datos de ensayos realizados en especies de Amphipoda, la primera resultó más sensible que Hyalella azteca (Nebeker et al, 1986, Wong et al, 1987e, Collyard et al, 1994e, Suedel et al, 1997, Gammarus aequicauda (Prato et al, 2006), Corophium insidiosum (Reish, 1993f, Prato et al, 2006 y Corophium orientale (Lera et al, 2008). Lo mismo puede decirse con respecto a Corophium volutator (Bat et al, 1998f) y Paramoera Walkeri (Dusquene et al, 2000); no obstante, Hyalella curvispina (García, 2008, experiencias (Prato et al, 2006, Giarratano et al, 2007.…”
Section: Efecto Del CD (Ii) Sobre Chlamydotheca Incisa Y Strandesia Bunclassified
“…Se compararon los resultados obtenidos en este trabajo con otras especies de crustáceos que se explicitan en la Tabla et al, 1995det al, , Guilhermino et al, 2000b. Por otro lado, al comparar la LC 50 de S bicuspis y C. incisa con la del anfípodo C. orientale, el decápodo Palaemonetes pugio y el anostraco Artemia salina (Whitting et al, 1996c, Liwarska-Bizukojc et al, 2005, Lera et al, 2008. Se observó que dichos ostrácodos fueron más tolerantes.…”
Section: Efecto Del CD (Ii) Sobre Chlamydotheca Incisa Y Strandesia Bunclassified